2020
DOI: 10.1111/1462-2920.15033
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between two quorum sensing‐regulated pathways, violacein biosynthesis and VacJ/Yrb, dictates outer membrane vesicle biogenesis in Chromobacterium violaceum

Abstract: Outer membrane vesicles (OMVs) are lipid nanoparticles released by Gram-negative bacteria, which play multiple roles in bacterial physiology and adaptation to diverse environments. In this work, we demonstrate that OMVs released by the environmental pathogen Chromobacterium violaceum deliver the antimicrobial compound violacein to competitor bacteria, mediating its toxicity in vivo at a long distance. OMVs purified by ultracentrifugation from the wild-type strain, but not from a violacein-abrogated mutant Δvio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 45 publications
1
25
0
5
Order By: Relevance
“…At the same time OMVs production was not interrupted. This observation is in line with recently published data: OMVs and violacein biosynthesis depends on LuxI/LuxR quorum sensing system and as was recently published ΔcviR (homolog of luxR) mutant of C. violaceum loss visible pigmentation due to dramatical drop in violacein production, while vascularization per cell in ΔcviR mutant reduced by only half because of alternative OMVs regulation [48]. Absence of pigmentation is the most noticeable phenotype of ΔluxR, while it is wellknown that inability to respond through LuxI/LuxR system leads to significant changes in other important processes and minimization of the cooperative traits.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…At the same time OMVs production was not interrupted. This observation is in line with recently published data: OMVs and violacein biosynthesis depends on LuxI/LuxR quorum sensing system and as was recently published ΔcviR (homolog of luxR) mutant of C. violaceum loss visible pigmentation due to dramatical drop in violacein production, while vascularization per cell in ΔcviR mutant reduced by only half because of alternative OMVs regulation [48]. Absence of pigmentation is the most noticeable phenotype of ΔluxR, while it is wellknown that inability to respond through LuxI/LuxR system leads to significant changes in other important processes and minimization of the cooperative traits.…”
Section: Discussionsupporting
confidence: 93%
“…We identified full vioABCDE operon in genome sequence of unpigmented isolate that gave us a reason to hypothesize regulatory nature of absence pigmentation in ChrSW isolate. Regulation of violacein production depends on quorum-sensing (QS) signals [48]. Closer investigation of genome region responsible for LuxI/LuxR regulatory QS pathway revealed deletion of large DNA fragment including luxR sequence that made impossible classical positive-feedback regulation of LuxI/LuxR system in response to AHL (Figure 3).…”
Section: Regulatory Nature Of Unpigmented Isolatementioning
confidence: 99%
“…Recent reports have found that several input signals, such as iron limitation, bile salts, and host entry, cause downregulation of the vac-J/yrb genes resulting in an increased OMV release that modulate bacterial adaptation to host conditions. Therefore, future works addressing the role of OMVs in C. violaceum virulence will be of particular interest [122].…”
Section: Biogenesismentioning
confidence: 99%
“…Even in bacteria such as Escherichia coli and Salmonella that do not produce AHLs (gram negative QS signalling molecule), it still possesses AHL response regulator protein, enabling it to respond to AHLs made by other bacteria. A third QS signalling molecule: Autoinducer-2 (AI-2), has been proposed as the signalling molecule used on an intra-species and inter-species level; facilitating communications between gram positive and negative bacteria [37][38][39]. It is important to note that although QS is essential for the formation of biofilms, the loss of this cell to cell communication system does not cause a lethal effect on bacterial cells [20].…”
Section: Quorum Quenchingmentioning
confidence: 99%